Posterior fossa ependymomas in children and adolescents - the state of the art - Marcos Devanir Silva da Costa; Carolina Torres Soares; Patricia Alessandra Dastoli; Jardel Mendonça Nicácio; Frederico Adolfo Benevides Silva; Maria Teresa de Seixas Alves; Michael Jenwei Chen; Andrea Maria Cappellano; Nasjla Saba Silva; Sergio Cavalheiro (Brazilian Society for Pediatric Neurosurgery, 2023)
Central nervous system tumors in pediatric patients represent the most frequent solid tumor type in this age group, especially ependymomas, which comprise 5% of childhood intracranial tumors, and occur mainly in the posterior fossa. The MEDLINE and ClinicalTrials databases were searched for studies on posterior fossa ependymomas, 64 studies met the search criteria.  Symptoms include ataxia, vertigo, headache, vomiting, cranial nerve palsies, or papilledema, resulting from intracranial hypertension due to obstruction of CSF circulation. Imaging examination often reveals posterior fossa ependymomas in the fourth ventricle or cerebellopontine angle; they may extend through the foramina of Luschka, Magendie, and/or magnum. These tumors cause a significant mass effect, displacing rather than invading the hidbrain, and may involve vessels or cranial nerves, making surgical resection difficult. Various radiological features have been studied to distinguish between ependymomas and other histological types, as well as between ependymoma subtypes.  The 2021 WHO classification of central nervous system tumors classifies ependymomas by location. Three types occur in the posterior fossa: subependymomas, PF-A, and PF-B. These are differentiated by the degree of DNA methylation and CpG islands, which can be assessed by immunohistochemical analysis with H3K27me3.  The consensus on the treatment of posterior fossa ependymomas in children advocates the maximum possible surgical resection, followed by radiotherapy in patients >1 year. Chemotherapy remains controversial, with no survival gain. Recent studies suggest molecular subgroups as an independent prognostic factor in posterior fossa ependymomas. The therapeutic challenge of ependymomas requires new treatment options, based on new technologies and molecular discoveries.